Dynamically tunable transmissive color filters using ultra-thin phase change materials - He, Q; Youngblood, N; Cheng, Z; Miao, X; Bhaskaran, H (Optical Society of America, 2020)
Structural color filters (i.e. plasmonics and nano-cavities) provide vivid and robust color filtering in applications such as CMOS image sensors but lack simplicity in fabrication and dynamic tuning. Here we report a dynamically tunable, transmissive color filter by incorporating an ultra-thin phase change layer inside a thin-film optical resonator. The transmitted color spectrum can be designed over the entire visible range and shifted by around 50 nm after phase transition. Angle dependence shows little color variation within a ±30° viewing angle. Crucially, only film deposition is required to fabricate our phase change color filter, showing great potential for large-scale and inexpensive production. The dynamically tunable color filter, described in this paper, could be a promising component in display, CMOS sensor, and solar cell technology.